Lactobacillus gasseri PA-3 reduces serum uric acid levels in patients with marginal hyperuricemia. (3rd April 2022) - Hamada, Toshihiro; Hisatome, Ichiro; Wakimizu, Takayuki; Kato, Masahiko; Gotou, Tamotsu; Koga, Atsuro; Endo, Yusuke; Taniguchi, Shin-ichi; Yamamoto, Kazuhiro; Ninomiya, Haruaki; Tsuboi, Hiroshi; Yamaguchi, Makoto; et al.
Abstract: Several studies have reported that Lactobacillus gasseri PA-3 reduces the level of serum uric acid (SUA) in patients with hyperuricemia. However, it remains unknown how PA-3 affects uric acid metabolism. In the present study, we examined effects of PA-3-containing yoghurt on uric acid metabolism in patients with marginal hyperuricemia. Sixteen patients with SUA > 357 μmol/L (marginal hyperuricemia) were enrolled. PA-3-containing yoghurt was administered for 8 weeks. Uric acid metabolism was evaluated just before and 8 weeks after the administration and at 4 weeks after the administration ended (post-administration). SUA levels after the administration were significantly lower than that before the administration and remained low at post-administration. Urinary uric acid concentration (Uur) after the administration were significantly lower than that before the administration. However, post-administration Uur levels were comparable to those before the administration. Therefore, PA-3-containing yoghurt significantly reduced the levels of SUA and Uur in patients with marginal hyperuricemia.